Konservasi Nilai-Nilai Pancasila Dalam Menguatkan National Character Building Mahasiswa - Susilo Tri Widodo dkk (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The conservation of Pancasila values is an effort to build pancasila values in every student in higher education, especially PGSD FIP UNNES students in order to have attitudes and behaviors that conform to the noble values of indonesian identity. The research method used is qualitatively descriptive. Descriptive research with pourposive sampling sample techniques. Research data sources are informants, activities, and documents. Data collection techniques through interviews, observations, questionnaires, document studies, focus group discussion, validity of data using trianggulasi and informant review. Analysis techniques are used with interactive flowing models. Further studies will be continued by creating a framework for the conservation model of Pancasila values. The results of the research that has been achieved are 1) the implementation of the conservation of Pancasila values in students of the DEPARTMENT OF PGSD FIP UNNES based on the data of the results of the study shows the percentage of implementation in each of these values namely the godliness value of 86.25%; humanitarian value 64.25%; union value of 82.00%; populist value 71.25%; and a justice score of 69.50%. 2) The obstacles faced in the conservation of Pancasila values are internal and external. 3) Pancasila's model of conservation of values is carried out to strengthen the national charcter building by referring to Thomas Lickona's theory which emphasizes on the three components of the formation of moral character knowing, moral feeling, and moral acting. The conclusion of this study is that it is necessary to optimize the conservation of Pacasila values in students in strengthening the national character building with a continuous or continuous programmatic model.